A low-exponent nonlinear fluid inerter-based damper for structural vibration control: Experiment and numerical investigation - Huating Chen; Fengyu Yang; Linfei Hao; Yanhui Liu; Tao Luo (Engineering Structures, 2026)

Arabidopsis MPK2 negatively regulates drought tolerance by balancing growth and stress responses - Yuzhen Li; Yi Feng; Na Li; Jisheng Li; Heng Zhou; Linfei Liu (Plant Science, 2026)

Simulation of an imperfect gas air gun wavelet on the basis of a unified theory for bubble dynamics - Quanchen Jia; Linfei Wang; Huaishan Liu; Lei Xing; Dong Zhang; Jin Zhang; Yanxin Yin (Ocean Engineering, 2026)

Stochastic mathematical modeling and data fitting for pine wilt disease prevention and control: a case study in China - Xiaohu Liu; Linfei Nie (Stochastic Environmental Research and Risk Assessment, 2026)

Long non-coding RNA MINCR silencing contributes to suppressed gemcitabine resistance in bladder cancer by blocking the ZEB1/PHGDH axis through microRNA-876-5p up-regulation - Linfei Xu; Yongfeng Lin; Liming Zhang; Xingzhang Lin; Sheng Liu (Journal of Molecular Histology, 2025)

Contribution of deep organic fluids to uranium mineralization in Cretaceous sandstones of the southwestern Ordos Basin, China - Linfei Qiu; Ziying Li; Feng He; Zhenqian Wu; Kunpeng Liu; Liang Zhang; Ning Mao; Tingting Wang; Lu Wang (Hydrogeology Journal, 2025)
In recent years, significant advancements have been achieved in uranium (U) prospecting within the Lower Cretaceous strata of the southwestern Ordos Basin, China. U deposits have been unearthed in Zhenyuan and Pengyang County, predominantly found within the Cretaceous sandstones of the Luohe and Huanhe formations. These ore-bearing strata primarily originate from arid environments, characterized by a deficiency of organic matter (OM). This deposit type manifests within lenticular, gray sandstone interbedded within red sandstone. Its genesis markedly diverges from oxidation-reduction sandstone-type U deposits, yet systematic studies on the properties of ore-forming fluids, particularly their sources and contributions to U mineralization, remain lacking. Core observations were conducted, and representative samples were collected for laboratory analysis. This study discerns the characteristics of ore-forming fluids within the U-bearing sandstone and deliberates the source of these fluids and their impact on U mineralization. Results indicate an abundance of flow-patterned , OM-rich U ores, derived from the deep mudstone rocks of the Yanchang Formation. The ore-forming fluids, characterized as OM-rich and low-temperature (130 to 180°C) hydrothermal fluids, originate from fluid discharge within the source rocks. Subsequently, ore-forming materials dissolve within these OM-rich fluids and migrate towards the oxidized sandstone in shallower regions. Significant changes in temperature and oxygen fugacity lead to fluid differentiation or cracking, facilitating U precipitation into U ores. The characteristics of Cretaceous U mineralization in the study area are consistent with the exudative model of sandstone-type U metallogenesis.

Ultrasonic pulse velocimetry of hydrate-bearing sediments using discrete element method - Mingxin Zhao; Huaishan Liu; Qing Ma; Anqi Jia; Lei Xing; Linfei Wang (Gas Science and Engineering, 2025)

Optimising microbial processes with nano-carbon/selenite materials: An eco-friendly approach for antibiotic resistance mitigation in broiler manure - Lizhi Li; Weikun Guan; Baohua Xiao; Qin He; Gangfu Chen; Jianzhong Wu; Zhigang Zhao; Feng You; Jinsheng Yang; Yue Xing; Lijun Zhou; Jinmeng Shi; et al. (Chemical Engineering Journal, 2024)

Diesel exhaust exposure induced squamous metaplasia of corneal epithelium via yes-associated protein activation - Xiaoya Ji; Yanting Li; Meike Liu; Linfei Chen; Xinglin Zhang; Mingyue Wang; Shuhan Tian; Lin Lu; Mingliang Zhang; Yuxin Zheng; Jinglong Tang (Chemosphere, 2024)

The effects of growth modifiers on the catalytic performance of hierarchical Pd/ZSM-23 bifunctional catalysts for n-hexadecane hydroisomerization - Jiazheng Sun; Shuxiang Xiong; Hailong Lin; Qiong Wu; Linfei Xiao; Zhenni Liu; Xiujie Li; Wei Wang; Wei Wu (Fuel, 2023)

Functional divergence of oligoadenylate synthetase 1 (OAS1) proteins in Tetrapods - Xiaoxue Wang; Jiaxiang Hu; Linfei Song; Enguang Rong; Chenghuai Yang; Xiaoyun Chen; Juan Pu; Honglei Sun; Chuze Gao; David W. Burt; Jinhua Liu; Ning Li; et al. (Science China Life Sciences, 2022)

Hair as a noninvasive biomarker of human exposure to the endocrine disruptors polybrominated diphenyl ethers: a meta-analysis - Xuemin Zhao; Linfei Liu; Jianhui Pang (Environmental Monitoring and Assessment, 2021)

Influence of Potassium Supply and Harvest Time on Selected Growth, Physiology, and Quality Factors of Ephedra sinica Stapf. - Anli Liu; Siqi Li; Jiayue Liu; Fuying Mao; Linfei Li; Nana Cen; Xueyan Fu; Yunsheng Zhao (Journal of Soil Science and Plant Nutrition, 2021)

Migration of impurity level reflected in the electrical conductivity variation for natural pyrite at high temperature and high pressure - Kaixiang Liu; Lidong Dai; Heping Li; Haiying Hu; Lei Wu; Yukai Zhuang; Chang Pu; Linfei Yang (Physics and Chemistry of Minerals, 2018)

Development of a multimetric index based on benthic macroinvertebrates for the assessment of urban stream health in Jinan City, China - Linfei Liu; Zongxue Xu; Xuwang Yin; Fulin Li; Tongwen Dou (Environmental Monitoring and Assessment, 2017)

Phase characteristic analysis of continuous depth air-gun source wavelet - Lei Xing; Huaishan Liu; Xilai Zheng; Xueqin Liu; Jin Zhang; Linfei Wang; Zhihui Zou; Yiming Xu (Journal of Ocean University of China, 2016)

Retrieving drill bit seismic signals using surface seismometers - Linfei Wang; Huaishan Liu; Siyou Tong; Yanxin Yin; Lei Xing; Zhihui Zou; Xiugang Xu (Journal of Earth Science, 2015)

Shallow water body data processing based on the seismic oceanography - Huaishan Liu; Yi Hu; Yanxin Yin; Linfei Wang; Siyou Tong; Hai Ma (Journal of Ocean University of China, 2013)